2019
DOI: 10.1007/jhep04(2019)169
|View full text |Cite
|
Sign up to set email alerts
|

Instabilities of thin black rings: closing the gap

Abstract: We initiate the study of dynamical instabilities of higher-dimensional black holes using the blackfold approach, focusing on asymptotically flat boosted black strings and singlyspinning black rings in D ≥ 5. We derive novel analytic expressions for the growth rate of the Gregory-Laflamme instability for boosted black strings and its onset for arbitrary boost parameter. In the case of black rings, we study their stability properties in the region of parameter space that has so far remained inaccessible to numer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
(226 reference statements)
0
6
0
Order By: Relevance
“…One might use blob rings to study black ring dynamics at large D as has been done for Myers-Perry black holes. It is known that thin rings are unstable to Gregory-Laflamme (GL) type non-axisymmetric fluctuations [5,46,47]. In the large D limit, the same instability was found in the effective theory on the ring coordinate [25].…”
Section: Jhep02(2021)131mentioning
confidence: 63%
See 2 more Smart Citations
“…One might use blob rings to study black ring dynamics at large D as has been done for Myers-Perry black holes. It is known that thin rings are unstable to Gregory-Laflamme (GL) type non-axisymmetric fluctuations [5,46,47]. In the large D limit, the same instability was found in the effective theory on the ring coordinate [25].…”
Section: Jhep02(2021)131mentioning
confidence: 63%
“…The elastic instability numerically found in D = 5 [5] is another interesting phenomenon, which deforms the ring keeping its thickness almost unchanged, in contrast to the GL instability. Recently, it was shown that thin black rings are free of this type of instability within the scope of the blackfold approximation [47]. 15 It is interesting to see if blob rings admit the elastic-type instability with or without the non-perturbative correction caused by the blob-blob interaction.…”
Section: Jhep02(2021)131mentioning
confidence: 99%
See 1 more Smart Citation
“…rings with small curvature radius, but is not observed for thin rings, i.e. rings with large curvature radius, [40,41].…”
Section: A Notations and Conventionsmentioning
confidence: 96%
“…Subsequently, we present the derivation of the blackfold perturbation equations used in the main text. For further discussion on embedding geometry and blackfold perturbation equation, see [27][28][29].…”
Section: Jhep11(2020)055 C Blackfold Perturbation Equationsmentioning
confidence: 99%